PENGATURAN DALAM PEMBERIAN REMISI TERHADAP NARAPIDANA ANAK BERLANDASKAN NILAI KEADILAN & KEPASTIAN HUKUM - Fery Hardiansyah; Mitro Subroto; Rian Sacipto (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
Indonesia as a state of law is obliged to carry out all of its activities in accordance with applicable law and play a role in achieving justice and legal certainty. Children who are in conflict with the law will undergo the process of the juvenile criminal justice system. As prisoners, children have a number of rights, namely rights as children themselves, as well as rights as prisoners. The right as a child prisoner, one of which gets remission. Remissions are given for the constitutional mandate that has been determined by the State through the Act and Presidential Decree. Remission is one of the important instruments for the criminal justice system in Indonesia, in accordance with its principle of re-socializing the community with the principle of protection. Remission has many good effects for child prisoners, to reduce the adverse effects that occur on children due to the criminal period that must be carried out and reduce the psychological burden of children who are growing and developing. The state exists to fulfill various children's rights, without exception the rights of children in conflict with the law. Fulfillment of rights includes an obligation to be carried out in accordance with the mandate of the law so that the protection of children applies in Indonesia. Remission is a right that must be granted in accordance with the terms and conditions set by the constitution based on the values of justice and legal certainty.